Application of DEA technique in SWOT analysis of oily sludge management using fuzzy data - H. Borgheipour; Z. Moghaddas; M. Abbassi; N. Abbaszadeh Tehrani (Global Journal of Environmental Science and Management)
The proper management of oily sludge from petroleum products storage tanks is necessary because inappropriate methods for dredging of tanks may result in high costs and increased environmental pollution. The purpose of the current study is to rank the strategies outlined by strengths, weaknesses, opportunities and threats analysis using data envelopment analysis model, which provides enriched insights into management of waste from dredging of tanks. As a result, with the use of strengths, weaknesses, opportunities and threat analysis, the strengths, weaknesses, opportunities, and threats were determined and some management strategies for oily sludge were obtained. Afterward, fuzzy data envelopment analysis was used to prioritize the strategies. Using experts' opinions, strategies can be ranked and prioritized by solving the data envelopment analysis model according to the acquired optimal solutions. An important point in this method is that experts' opinions are also incorporated into the analysis. Sixteen strategies are presented based on the strengths, weaknesses, opportunities and threat analysis and prioritized based on fuzzy data envelopment analysis. Strategies number 14 and 10, based on weakness-opportunities and strengths-threats respectively are of first priorities. Therefore, the strategies such as development of executive instructions and guidelines, elaboration of duties of managers regarding waste management and construction of a suitable and centralized site for storing oily sludge according to environmental requirements could be strategically useful for the management of oily sludge from storage tanks.